Multibeam spherotron - A. A. Kurayev; V. V. Matveyenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
The article proposes two types of multibeam spherotron-diotron based on a two-spherical resonator (an early article suggested a spherotron-diotron with non-synchronous interaction on a bi-spherical resonator, where the electron beam in this generator passes along the resonator z axis from the outer sphere to the inner one and interacts with the longitudinal (axial) electric resonator field). The first spherotron type has electron beams going from outer to inner sphere with slope ϧ about the z-axis: ϧ=0, π/8, π/4. The electrons interact with the resonator field through the emergence of quadratic forces in the field increasing along the electron motion. The second type (inverted spherotron) has electron beams located in half arc of the equatorial resonator plane, and the electrons move from the inner sphere to the outside. The interaction in it is carried out due to the spatial electron phasing. Both spherotron types achieve efficiency of 30 % at ultra-high pulse power and tens of kuloampère of total beam currents. The data presented in the article indicate the prospects of broad application for the inverted spherotron by the following indicators: extreme ease of design; no precision gratings or combs are required with a step significantly shorter than the wavelength; no focusing magnetic systems are required; electronic efficiency from 26 to 45 % is ensured. Note that the spherotron is fundamentally a highpower device (10-100 MW in a 1-10ns pulse) for in order to maintain the efficiency of non-synchronous interaction, one needs a high strength of the electromagnetic field, which is achieved only with a high-power device.